Conceptual bases of forecasting of effective use of economic capacity of the Carpathian region - Машіка, Ганна (Human Geography Journal, 2016)
The research is carried out in the field of economic geography. The aim of this article is to raise the efficiency of economic potential of Carpathian region. The need for forecasting natural resource is described with particular attention. This paper proposes a new approach to the study of the region's economic potential, which is the object of the prediction. Content potential acquires new characteristics, which are dynamism and discrete.Studying the properties of types of resources gives the possibility of constructing system of indicators for forecasting of efficiency use the Carpathian’s potential. System of indicators must meet the following requirements: to comply with the norms and standards in Ukraine; do not conflict with the range of official statistics; be consistent with international guidelines on the assessment of the effective use of natural resources in the region. Special attention was paid to the methods of prediction of economic potential. Two basic methods according to which high level of reliability of forecast may be distinguished were singled out. Firstly, extrapolation method is recommended for data forecasting. Secondly, expert assessments are used for correction calculations. The results of the study are useful for development of regional and local programs of preservation and use of natural resources.